The Role of Islamic Microfinance Institutions in Enhancing Income and Welfare of Microenterprises in Aceh Province: A Case Study of Baitul Qiradh - Jauharil Maknuni; Erni Wiriani; Masitah; Cut Siti Maisarah; Selvi Mai Hetti (JIM: Jurnal Ilmiah Mahasiswa, 2026)
This study aims to analyze the role of Islamic Microfinance Institutions (LKMS), particularly Baitul Qiradh, in enhancing the income and welfare of micro-entrepreneurs in East Aceh Regency, Aceh Province. A qualitative descriptive approach was employed, using data collection techniques such as in-depth interviews, observations, and documentation. The participants consisted of Baitul Qiradh managers, micro-entrepreneurs, and community leaders familiar with the development of Sharia-based economic activities. The findings reveal that Baitul Qiradh plays a strategic role across three major dimensions: economic, social, and spiritual. Economically, financing through mudharabah and musyarakah contracts has improved access to capital, income levels, and business stability. Socially, entrepreneurship training and mentoring programs have strengthened solidarity, collaboration, and social networks among business actors. Spiritually, the implementation of Islamic principles such as honesty, trustworthiness, and justice has shaped ethical and equitable business behavior. Overall, this study concludes that Baitul Qiradh functions not only as a financial institution but also as an agent of economic and social empowerment based on Islamic values, contributing to sustainable local economic development